Supramolecular Polysulfide Polymers with Metal‐Ligand Interactions. Issue 5 (3rd February 2022) - Yamagishi, Yuki; Kobayashi, Yuichiro; Horiguchi, Akiyoshi; Kitano, Daiki; Yamaguchi, Hiroyasu
Abstract: We report the first preparation of a supramolecular polysulfide polymer using metal‐ligand interactions. The supramolecular polysulfide polymer was prepared by introducing 2, 2'‐bipyridine (bpy) at both ends of linear sulfur and linking the bpy with Cu 2+ . The molecular weight of the supramolecular polysulfide polymer was higher than polysulfide polymer obtained via conventional polymerization. Disassembly and re‐assembly of the supramolecular polysulfide polymers were controlled by de‐metalation of Cu 2+ from the complex between bpy and Cu 2+ and re‐formation of the complex with the addition of chelating agents and Cu 2+, respectively. Abstract : A supramolecular polysulfide polymer using metal‐ligand interactions was synthesized for the first time in the world. The supramolecular polysulfide polymer was prepared by introducing 2, 2'‐bipyridine (bpy) at both ends of linear sulfur and linking the bpy with Cu 2+ . Disassembly and re‐assembly of the supramolecular polysulfide polymers were controlled by de‐metalation of Cu 2+ from the complex between bpy and Cu 2+ and re‐formation of the complex with the addition of chelating agents and Cu 2+, respectively.